Analisis Penentuan Pusat Pelayanan Perkotaan Di Wilayah Provinsi Sumatera Utara - Pratama, Lucky Satria; Wahyuni, Sri; Sapahira, Prety; Yani, Cindy Indah; Kartika, Kartika; Faiz, Muhammad; Suta, Roffi Rivaldo Arya; Wardhana, Wahyu Habib (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This analysis was carried out to identify districts/cities that could be grouped into candidate service centers based on educational, economic, health and social facilities. The type of data used in this research is secondary data. The data collection method used was a literature review taken from the Central Statistics Agency (BPS). Next, the data was analyzed using scalogram analysis and centralization index analysis. The results of this research show that the areas that are urban service centers are located in Hierarchy I, namely the Regency/City of Tapanuli Utara, Toba, Dairi, Nias Selatan, Pakpak Barat, Samosir, Serdang Bedagai, Nias Utara, Nias Barat, Sibolga, Pematangsiantar, Tebing Tinggi, Medan, and Binjai. This district/city can be used as an urban service center in the North Sumatra Province region.